1991
DOI: 10.1093/brain/114.1.405
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Action in ‘Visual Form Agnosia’

Abstract: A single case study of a patient with 'visual form agnosia' is presented. A severe visual recognition deficit was accompanied by impairments in discriminating shape, reflectance, and orientation, although visual acuity and colour vision, along with tactile recognition and intelligence, were largely preserved. Neuropsychological and behavioural investigations have indicated that the patient is able to utilize visual pattern information surprisingly well for the control of hand movements during reaching, and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
195
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 551 publications
(213 citation statements)
references
References 26 publications
9
195
1
1
Order By: Relevance
“…D.F. failed in visual perceptual tasks while her visuomotor performance was not impaired (Milner et al, 1991). A recent study (Schenk, 2006) revealed that the discrepancy in her behavior was not due to different response modes, but rather due to deficits in different spatial representations (Himmelbach et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…D.F. failed in visual perceptual tasks while her visuomotor performance was not impaired (Milner et al, 1991). A recent study (Schenk, 2006) revealed that the discrepancy in her behavior was not due to different response modes, but rather due to deficits in different spatial representations (Himmelbach et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, whereas visual illusions may affect our perception of an object's size or position, it has been reported that visually guided reaching can be relatively immune from such perceived distortions (38,39). Similarly, patients with brain damage may be able to act appropriately on objects despite dramatic perceptual disruption that would seem to preclude such accurate actions (40). Furthermore, neurons in some sensorimotor areas are activated by visual stimuli more quickly than neurons in many areas of visual cortex (41), indicating that sensorimotor mechanisms can be initiated without relying on a hierarchy of visual processing to feed them perceptual information.…”
Section: Discussionmentioning
confidence: 99%
“…'s brain that provided the important clue as to how these different mechanisms might be realized in neural circuitry. An early structural MRI [16] showed evidence of extensive bilateral damage in the ventral visual stream. More recent high-resolution MRI scans [17,18] have confirmed this ventral-stream damage but revealed that the lesions are focused in the lateral occipital cortex (area LO), an area that we now know is involved in the visual recognition of objects, particularly their geometric structure [19].…”
Section: Neuropsychological Dissociations Between Perception and Actionmentioning
confidence: 99%